Light absorption, fluorescence properties and sources of brown carbon aerosols in the Southeast Tibetan Plateau. (February 2020) - Wu, Guangming; Wan, Xin; Ram, Kirpa; Li, Peilin; Liu, Bin; Yin, Yongguang; Fu, Pingqing; Loewen, Mark; Gao, Shaopeng; Kang, Shichang; Kawamura, Kimitaka; Wang, Yongjie; et al.
Abstract: Brown carbon (BrC) has been proposed as an important driving factor in climate change due to its light absorption properties. However, our understanding of BrC's chemical and optical properties are inadequate, particularly at remote regions. This study conducts a comprehensive investigation of BrC aerosols in summer (Aug. 2013) and winter (Jan. 2014) at Southeast Tibetan Plateau, which is ecologically fragile and sensitive to global warming. The concentrations of methanol-soluble BrC (MeS-BrC) are approximately twice of water-soluble BrC (WS-BrC), demonstrating the environmental importance of water-insoluble BrC are previously underestimated with only WS-BrC considered. The mass absorption efficiency of WS-BrC (0.27–0.86 m 2 g −1 ) is lower than those in heavily polluted South Asia, indicating a distinct contrast between the two sides of Himalayas. Fluorescence reveals that the absorption of BrC is mainly attributed to humic-like and protein-like substances, which broaden the current knowledge of BrC's chromophores. Combining organic tracer, satellite MODIS data and air-mass backward trajectory analysis, this study finds BrC is mainly derived from bioaerosols and secondary formation in summer, while long-range transport of biomass burning emissions in winter. Our study provides new insights into the optical and chemical properties of BrC, which may have implications for environmental effect and sources of organic aerosols. Graphical abstract: Image 1 Highlights: Methanol-soluble BrC is more abundant than water-soluble BrC. Protein- and humic-like substances are the main chromophores in BrC. BrC is mainly derived from bioaerosols and secondary formations in summer. In winter, biomass burning emissions are the dominant sources of BrC. Abstract : Optical properties and organic tracers demonstrate that BrC is derived from bioaerosols in summer, while biomass burning emissions in winter.